ANALISIS BERPIKIR KRITIS MATEMATIS DALAM PEMECAHAN MASALAH DI SMK NEGERI 4 KUPANG - Sahura Puas; Ryan Nizar Zulfikar; Nia Kurniaty Rukman (MEGA: Jurnal Pendidikan Matematika, 2023)
This study aims to analyze the ability to think critically mathematically in solving problems at class IX at SMK Negeri 4 Kupang. This type of research is descriptive research with a qualitative approach. The data collection technique used was a written test with a total of three description questions and interviews. The subjects in this study were three students who were selected from 30 students in class IX at SMK Negeri 4 Kupang. Among them are students with high critical thinking skills, students with moderate critical thinking skills and students with low critical thinking skills to be interviewed regarding the answers they have written and explore critical thinking from the subject. In analyzing the data there are several parts, namely data reduction, data display, and consultation drawing/verification. Data reduction (Data reduction), Data presentation (Data display). The results of this study indicate that students who have high abilities (R1) fulfill the six indicators of critical thinking. Students who have moderate abilities (R3) who meet several indicators of the six indicators of critical thinking. Among them, a) Focus, b) Reason, c) Inference, d) Situation, e) Clarity. Students who have low abilities (R28) only fulfill a few critical thinking indicators, including, a) Focus, b) Situation, c) Clarity.